2021
DOI: 10.3389/fonc.2021.639438
|View full text |Cite
|
Sign up to set email alerts
|

MBOAT7-TMC4 rs641738 Is Not Associated With the Risk of Hepatocellular Carcinoma or Persistent Hepatitis B Infection

Abstract: ObjectiveA hot genetic variant, rs641738 within the membrane-bound O-acyltransferase domain containing 7(MBOAT7) and transmembrane channel-like 4 (TMC4), was recently reported to be associated with several liver diseases. However, the results remain controversial. Therefore, this study aimed to explore the role of MBOAT7-TMC4 rs641738 in the risk of hepatocellular carcinoma (HCC) and persistent hepatitis B virus (HBV) infection.MethodsWe first conducted a case-control study that included 779 HCC cases and 1412… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…A recent study on a Thai cohort composed of HCC patients with different etiological backgrounds did not reveal any association between the MBOAT7 rs641738 polymorphism and the development of HCC 71 . The same MBOAT7 rs641738 variant did not have a statistically significant association with advanced liver stiffness 72,73 or hepatitis C virus‐induced liver cirrhosis, probably due to the etiological heterogeneity of the liver cirrhosis cohort and to a small number of patients within the subgroup analysis 68,74 …”
Section: Mboat7 Genetic Variation and Chronic Liver Disease In Humansmentioning
confidence: 88%
See 1 more Smart Citation
“…A recent study on a Thai cohort composed of HCC patients with different etiological backgrounds did not reveal any association between the MBOAT7 rs641738 polymorphism and the development of HCC 71 . The same MBOAT7 rs641738 variant did not have a statistically significant association with advanced liver stiffness 72,73 or hepatitis C virus‐induced liver cirrhosis, probably due to the etiological heterogeneity of the liver cirrhosis cohort and to a small number of patients within the subgroup analysis 68,74 …”
Section: Mboat7 Genetic Variation and Chronic Liver Disease In Humansmentioning
confidence: 88%
“…This new variant might influence MBOAT7 mRNA expression and, therefore, its hepatic protein expression, suggesting that the rs641738 C>T may not be the causal variant linking MBOAT7 to SLD 66 . On the other hand, several studies showed that neither heterozygous nor homozygous carriage of the MBOAT7 rs641738 variant confer any increased risk of HCC development or HBV infection persistency or clearance 67–69 …”
Section: Mboat7 Genetic Variation and Chronic Liver Disease In Humansmentioning
confidence: 99%
“…Furthermore, two studies focused on HCC arising from NAFLD[ 12 ] or metabolic dysfunction-associated fatty liver disease[ 13 ], while another two[ 9 , 14 ] investigated a mixed cohort of NAFLD, viral, and alcohol-related HCC. One study[ 15 ] encompassed HCC occurring in the context of compensated cirrhosis (HCV or alcohol), and one[ 16 ] did not specify the particular characteristics of the included patient cohort. The genetic analysis techniques employed were diverse, with the TaqMan genotyping method being utilized in most studies ( n = 5), with one study employing the MassARRAY[ 16 ] and two[ 12 , 13 ] employing United Kingdom Biobank Axiom array methodologies.…”
Section: Resultsmentioning
confidence: 99%
“…However, the rs641738 T allele was not associated neither with HCC risk nor HBV infection in Chinese patients. ( 122 ).…”
Section: Managing Chronic Liver Disease Using a Permed-nut Approachmentioning
confidence: 99%